2023
DOI: 10.3389/fnins.2023.1202932
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic resting-state brain activity patterns of table tennis players in 7-Tesla MRI

Abstract: Table tennis involves quick and accurate motor responses during training and competition. Multiple studies have reported considerably faster visuomotor responses and expertise-related intrinsic brain activity changes among table tennis players compared with matched controls. However, the underlying neural mechanisms remain unclear. Herein, we performed static and dynamic resting-state functional magnetic resonance imaging (rs-fMRI) analyses of 20 table tennis players and 21 control subjects using 7T ultra-high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…However, specific studies have yet to be found where the technical-tactical response of TT is analyzed in terms of the development of brain processes combined with their differences between sexes. The neurological adaptations between male and female players differ depending on the years of deliberate practice and continuous learning in a specific domain [50,51]. Both processes alter functional brain activity, which is associated with optimal sport behavioral performance and differentiated because of different training designs [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, specific studies have yet to be found where the technical-tactical response of TT is analyzed in terms of the development of brain processes combined with their differences between sexes. The neurological adaptations between male and female players differ depending on the years of deliberate practice and continuous learning in a specific domain [50,51]. Both processes alter functional brain activity, which is associated with optimal sport behavioral performance and differentiated because of different training designs [51].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies solely relied on functional connectivity and effective connectivity to analyze the connection relationships between local brain regions. However, delving into the topological properties of the whole brain network has provided a deeper understanding of this connectivity [ 33 , 34 , 35 ]. The examination of whole-brain topological properties unveils the overall structure and characteristics of the brain network, along with the connection patterns and topological features among diverse brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with advancements in human brain connectomics, it has become evident that the human brain does not operate in isolation; rather, it exhibits close connections between different regions and operates in coordination through specific connection patterns with efficient network transmission characteristics [32]. Previous investigations into brain networks among TTAs have primarily emphasized functional connectivity and efficiency connectivity [33,34]. For instance, Li et al (2023) [33] observed reduced static functional connectivity in the right middle temporal gyrus and left inferior parietal gyrus among individuals with TTAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation